Rice cultivation handbook - Lengewa, Catherine; Mikhala, Audrine; Aura, Sylvester; Amuda, Alex; Yila, Jummai; Bomuhangi, Allan; Nchanji, Eileen (2024)
To address the persistent challenge of limited access to quality agricultural inputs, partic- ularly high-quality seeds in Uganda, a social and behavioral strategy was developed under the CGIAR Seed Equal Initiative activities under work package 6. Though agriculture serves as a cornerstone of Uganda’s economy, employing 70% of the labor force and covering half of the national land area. Smallholder farmers, comprising 90% of the farming commu- nity, face barriers to accessing quality seeds hindering agricultural productivity and food security. This activity led by the International Rice Research Institute (IRRI) and the Alliance of Bioversity International and CIAT in collaboration with the Centre for Behaviour Change and Communication (CBCC), focuses on improving seed access in Eastern Uganda, with a specific emphasis on Butaleja District. We aimed to empower smallholder farmers, women, and youth, enhance seed access and utilization, and contribute to increased agricultural productivity, livelihoods, and food security in Butaleja District and beyond. By implementing evidence-based strategies and fostering collaboration among stakeholders, we aim to create an inclusive and sustainable seed system that benefits all members of the agricultural community.